2014
DOI: 10.5901/mjss.2014.v5n9p697
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Domestic Work Phenomenon

Abstract: One of the fastest growing informal vocations in the world

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…For domestic work which is nonorganizational and non-institutional, it is expected that hours of work should be mutually agreed by the employer and domestic servant. However, studies (such as Afolabi, n.d.;Odeku, 2014) have…”
Section: Long Hours Of Workmentioning
confidence: 99%
See 1 more Smart Citation
“…For domestic work which is nonorganizational and non-institutional, it is expected that hours of work should be mutually agreed by the employer and domestic servant. However, studies (such as Afolabi, n.d.;Odeku, 2014) have…”
Section: Long Hours Of Workmentioning
confidence: 99%
“…Past studies (e.g. Akinrimisi, 2003;Nesbitt-Ahmed, 2016;Odeku, 2014;Okafor, 2009) have found that domestic workers, especially the live-in workers, in Nigeria are subjected to work long hours.…”
Section: Long Hours Of Workmentioning
confidence: 99%